The Role of Freshwater Forcing on Surface Predictability in the Gulf of Mexico. Issue 5 (16th May 2022) - Sun, Daoxun; Bracco, Annalisa; Liu, Guangpeng
Abstract: The potential predictability of fields at the ocean surface in the northern Gulf of Mexico (GoM) is investigated through five ensembles of regional ocean simulations between 2014 and 2016. The ensembles explore two horizontal resolutions and different representations of the riverine inflow, and focus on the interactions between the Loop Current system (LCS) and the riverine system. The potential predictability of the surface fields is high when simulated by an ocean‐only model forced by appropriate atmospheric forcing and boundary conditions, and the ensembles simulate similar LCS behavior up to 5 months. The ensemble spread provides a mean to quantify the potential predictability. The ensembles confirm that LCS‐riverine interactions are modulated by the LC mesoscale variability. The relationship is two‐ways, with the LCS being influenced by—And not only influencing—The freshwater plume. Whenever the freshwater flux is strong, the northward extension of the LCS is constrained by the intensified salinity fronts. This influence is slightly stronger if the riverine inflow is simulated in an active fashion with a meridional velocity component proportional to the flux. Sea surface temperature (SST) and salinity (SSS) predictability have opposite seasonality in their signal, with the SST (SSS) being more predictable in summer (winter). Partially resolving submesoscale instabilities and improving the realism of the riverine fluxes' representation causes the spread to increase, especially in SST. When increasing resolution, the spread increases also for surface vorticity due to feedbacks between the mesoscale and submesoscale circulations. The intraseasonal and interannual signal in vorticity is however similar among ensembles. Plain Language Summary: In this work we ask the questions: How predictable may be the circulation and the sea surface fields in the northern Gulf of Mexico (GoM), and what is the role of the riverine input? Under the assumption of a nearly perfect model and known atmospheric forcing and oceanic boundary fields, we simulate the GoM circulation through five groups of simulations with similar set‐ups (ensembles) which members differ only in their initial conditions. Each ensemble spans 32 months and we explore two horizontal resolutions and different representations of the riverine inflow. The predictability of the main current in the GoM, the so‐called Loop Current, is high under the conditions of our simulations. The northward extension of the Loop Current, however, is influenced by the riverine input and its representation. This influence is stronger if the riverine inflow is simulated accounting for a meridional velocity component proportional to the freshwater flux. The sea surface temperature (SST) field is more predictable in Summer, and the salinity (SSS) in winter. Increasing model resolution, on the other hand, decreases the predictability due to feedbacks between the mesoscale (several tens of kilometers in scale) and submesoscale (less than five km in scale) circulations. Key Points: The interaction of the Loop Current (LC) system and the river input in the northern Gulf of Mexico is two ways The interaction depends on model resolution and riverine input configuration Spread of Sea surface temperature and Sea surface salinity show opposite seasonality. Increasing spatial resolution decreases the predictability of surface relative vorticity